Terrestrial Megafauna Response to Drone Noise Levels in Ex Situ Areas - Mesquita, GP; Mulero-Pázmány, Margarita Cristina; Wich, S; Rodríguez Teijeiro, JD (My University, 2022)
Drone use has significantly grown in recent years, and there is a knowledge gap on how the noise produced by these systems may affect animals. We investigated how 18 species of megafauna reacted to drone sound pressure levels at different frequencies. The sound pressure level on the low frequency generated by the drone did not change the studied species’ behavior, except for the Asian elephant. All other studied species showed higher noise sensitivity at medium and high frequencies. The Asian elephant was the most sensitive species to drone noise, mainly at low frequencies. Felines supported the highest sound pressure level before showing behavioral reactions. Our results suggest that drone sound pressure levels in different frequencies cause behavioral changes that differ among species, which is relevant to assessing drone disturbances in ex situ environments. The findings presented here can help to reduce drone impact for target species and serve as an experimental study for future drone use guidelines.
Keywords: Aviones sin piloto; Behaviour; Impact